Large-scale network simulation techniques examples of TCP and OSPF models. - Yaun, Garrett R. (Computer communication review.)
Simulation of large-scale networks remains to be a challenge, although various network simulators are in place. In this paper, we identify fundamental issues for large-scale networks simulation, and porpose new techniques that address them. First, we exploit optimistic parallel simulation techniques to enable fast execution on inexpensive hyper-threaded, multiprocessor systems. Second, we provide a compact, light-weight implementation framework that greatly reduces the amount of state required to simulate large-scale network models. Based on the proposed techniques, we provide sample simulation models for two networking protocols: TCP and OSPF. We implement these models in a simulation environment ROSSNet, which is an extension to the previously developed optimistic simulator ROSS. We perform validation experoments for TCP and OSPF and present performance reuslts of our techniques by simulating OSPF and TCP on a large and realistic topology, such as AT&T's US network based on rocketfuel data. The end result of these innovations is that we are able to simulate million node network tolopgies using inexpensive commercial off-the-shelf hyper-threaded multiprocessor systems consuming less than 1.4 GB of RAM in total.